Feasibility study of the (α,α'γ) reaction at θlab = 0º using the K600 magnetic spectrometer - Erasmus, Wade Luke (Stellenbosch : Stellenbosch University, 2015)
Thesis (MSc)--Stellenbosch University, 2015.